APLIKASI ENKRIPSI DENGAN ALGORITMA RIVEST SHAMI ALDEMAN (RSA) DAN PARITY BIT CODING UNTUK FILE MULTIMEDIA - Usanto Usanto (Institut Teknologi dan Bisnis Swadharma, 2022)
Encryption is the most effective way to obtain data security. In order to read the encrypted file, we must have access to a password that will allow us to decrypt the message. Data that is not encrypted is called plain text, while the encrypted one is called cipher text. As for steganography is the process of hiding data in digital files so that people do not think that if there are digital files there is no message. If these two processes are in combination then the message will be more secure. For this reason, it is necessary to make an application to store messages in images with encryption in the first process. Many methods are used to recognize cryptography, one of which is the RSA method. The use of this method aims to find out how cryptography works and the systems contained in the cryptographic process. This cryptography and steganography application uses an application called Eclipse which is commonly used to create android mobile applications